(untitled) (Revista de Ciências Agroveterinárias, 2004)
The aim of this study was to verify by tests “in vitro” the immersion time of engorged female that showed better correlation with the efficacy of the acaricides on field tests. The following acaricides were used: 0,025% amitraz, 0,01% cypermethrin, 0,005% alfamethrin, and 0,0025% deltamethrin in different immersion times (2,5; 5; 10 minutes). For the field test, engorged female collected from bovine one hour after dipping them with the acaricides were used (except amitraz, that was 30 minutes). The data were analyzed statistically using the Kruskal- Wallis test at 0.05% of significance. The average percentage of efficiency was: amitraz 99.47%, 98.86%, and 99.34%; cypermethrin 67.70%, 82.64%, 84.95%, and 70.16%; alfamethrin 97.24%, 100%, 99.98%, and 92.68%, deltamethrin 99.89%, 100%, 99.73%, and 70.10%; respectively, to the immersion time of 2.5, 5, 10 minutes and the field test. There was no statistic difference between the immersion times of 5 and 10 minutes in all the four acaricides. There was difference between 2.5 and 10 minutes for cypermethrin. The comparison between field test efficiency and “in vitro” immersion time test” showed differences in at least one of them, for all the acaricides.